1997
DOI: 10.1117/12.271506
|View full text |Cite
|
Sign up to set email alerts
|

<title>Feature space trajectory representation for active vision</title>

Abstract: A new feature space trajectory (FST) description of 3-D distorted views of an object is advanced for active vision applications. In an FST, different distorted object views are vertices in feature space. A new eigen-feature space and Fourier transform features are used. Vertices for different adjacent distorted views are connected by straight lines so that an FST is created as the viewpoint changes. Each different object is represented by a distinct FST. An object to be recognized is represented as a point in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…where the PDF for x conditioned on class is obtained by multiplying the PDF for x conditioned on class and pose by the PDF for the pose parameter and integrating over t9 19) po (19)dO (7) The unconditional PDF for x, p,, (x) in Eq. (6), is obtained using the total probability theorem [46] as…”
Section: Classification and Classification Confidencementioning
confidence: 99%
See 1 more Smart Citation
“…where the PDF for x conditioned on class is obtained by multiplying the PDF for x conditioned on class and pose by the PDF for the pose parameter and integrating over t9 19) po (19)dO (7) The unconditional PDF for x, p,, (x) in Eq. (6), is obtained using the total probability theorem [46] as…”
Section: Classification and Classification Confidencementioning
confidence: 99%
“…We consider the FST representation of 3D distorted views of an object as a component of active vision system [7] that uses data from simple and inexpensive sensors (2D CCD cameras vs. 3D range sensors). In this paper, we describe new algorithms using the FST representation and neural network processor, that determine the best object viewpoints to use to improve the class decision or pose estimates.…”
Section: Fst Neural Networkmentioning
confidence: 99%
“…Optic flow has been applied by Shirai et al [31], Allen et al [1] and Papanikolopoulos [27]. Sipe et al [32], Nayar et al [24] and Deguichi [6] used eigenfeatures for 3-dof positioning and tracking.…”
Section: Image Featuresmentioning
confidence: 99%
“…In the field of computer vision, Principal Component Analysis (PCA) is best known as a method for image compression, feature detection, and pattern recognition. Recently, however, several authors have demonstrated its usefulness for pose estimation [24,32,6]. Given a set of multidimensional data samples, the aim of PCA is to determine a reduced orthonormal basis whose axes are oriented in the directions of maximum variance of the data in each dimension, and then project the data onto this new basis.…”
Section: Geometric Moment Descriptorsmentioning
confidence: 99%
“…2). The ability of the FST to utilize a reduced number of object views gives it a major advantage over other distorted object representations: whether the FST is constructed from a prototype object or a computer aided design (CAD) model, a continuum of training views is possible and some means of selecting views is necessary [5,6].…”
Section: Introductionmentioning
confidence: 99%